2020
DOI: 10.1002/rcm.8986
|View full text |Cite
|
Sign up to set email alerts
|

High‐spatial‐resolution measurements of iron isotopes in pyrites by secondary ion mass spectrometry using the new Hyperion‐II radio‐frequency plasma source

Abstract: Rationale: Iron isotopic signatures in pyrites are considered as a good proxy to reconstruct paleoenvironmental and local redox conditions. However, the investigation of micro-pyrites less than 20µm size has been limited so far by analytical techniques. The development of the new brighter radio-frequency plasma ion source (Hyperion-II source) enhances the spatial resolution by increasing the beam density 10 times compared to the Duoplasmatron source.Methods: Here we present high spatial resolution measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
(252 reference statements)
0
11
0
Order By: Relevance
“…Kang et al 16 developed a related but slightly different approach. They immobilised Ln labelled (with 159 Tb, 165 Ho, 175 Lu) DNA strands on streptavidin-modied magnetic beads.…”
Section: Glossary Of Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al 16 developed a related but slightly different approach. They immobilised Ln labelled (with 159 Tb, 165 Ho, 175 Lu) DNA strands on streptavidin-modied magnetic beads.…”
Section: Glossary Of Abbreviationsmentioning
confidence: 99%
“…This resulted in v 56 Fe reproducibility of AE0.1& (2SD) on pyrite, manganite, hematite and chalcopyrite. Improvements in Fe isotope measurements by SIMS was the subject of a study by Decraene et al 175 They used a new RF plasma ion source, Hyperion-II, which increased the ion beam density by an order of magnitude compared to a conventional Duoplasmatron source. The aim of the study was to enable measurement of micro-pyrites, which are less than 20 mm, and results indicated that reproducibility for v 56 Fe was AE0.25& (2SD) on the Balmat pyrite standard.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 99%
“…Therefore, the development of well-characterized natural standards is critical for accurate micro-beam analysis of Fe isotope analyses in pyrite. Before our study, one sintering pyrite material PAS-Py600 and several natural pyrite standards, such as Balmat, 35,64,65 JMC, 66 SpainCr, 55 Aa018, 59 have been used for micro-beam analyses of Fe isotopic composition (Table 1). It should be noted that some degree of natural variation is expected and observed in all these pyrite standards, which depends in part on the number/scale of characterization tests.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation MC-ICP-MS (LA-MC-ICP-MS) and secondary ion mass spectrometry (SIMS) are powerful micro-beam techniques for in situ Fe isotopic analyses in pyrite. 34,35,[55][56][57][58][59][60] The micro-beam technique is capable of resolving Fe isotopic variations between natural minerals commonly present as thin lamellae in iron meteorites, micron scale phases in sedimentary, and zonation in hydrothermal deposits. However, both LA-MC-ICP-MS and SIMS analyses generate isotopic ratios that have been fractionated during the examinations, and this fractionation is matrixdependent (e.g., ref.…”
Section: Introductionmentioning
confidence: 99%
“…21,23 SIMS has been used for in-situ Fe isotope determination with high spatial resolution. 19,24 However, the significant effects of matrix and crystal orientation of some high-symmetry minerals, such as Fe isotope analysis of magnetite (Fe3O4), have limited its application. 25 In contrast, the effects of crystal orientation do not affect the LA-MC-ICP-MS analysis.…”
Section: Introductionmentioning
confidence: 99%